COVID-19 Stress on Mental and Hair Health: A Marker for Diseases in the Post-Pandemic Era - Accorsi, Daniela Xavier; Dos Santos, Ingrid Aparecida Mendes [UNESP]; Accorsi, Juliana Xavier; Abelan, Ursulandréa Sanches [UNESP]; Martin Júnior, Celso [UNESP]; Bohac, Silvia; Bumiller-Bini, Valéria; Boldt, Angelica Beate Winter; Chin, Chung Man [UNESP] (Bentham Science Publishers, 2022)
The seriousness of the COVID-19 pandemic with accumulating stress factors, including lack of pharmacotherapy, quarantine, social distancing, delay of vaccination, and economic uncertainties, may foster fear and psychiatric disorders that can precipitate or aggravate hair/scalp disease. Hair loss can lead to decreased self-esteem, potentiating the negative effects on social life and generating a vicious cycle of stress during the pandemic. The relationship between environment and behavior can also trigger epigenetic changes in diseases, which may influence the health of the next generations. In this review, we describe the interaction between the physiological mechanisms of stress on hair follicles and hair disorders and openly discuss during pandemic/post-pandemic (not genetically determined but epigenetically triggered) hair loss as a point of concern as a health marker for further development of chronic diseases, such as diabetes, obesity, psychiatric disorders, and others.
Keywords: COVID-19; epigenetics; hair loss; mental health; post-pandemic; stress